Survival of Kamchatka pink salmon as result of combined influence of density regulation and environmental factors - Mark G. Feldman; Eugeny A. Shevlyakov (Известия ТИНРО)
Dynamics of stock abundance and survival is similar for the pink salmon populations from East Kamchatka and West Kamchatka, obviously because of the same large-scale environmental factors influence, as the Pacific Decadal Oscillation (PDO) and the Western Pacific pattern (WP) that correlate significantly with the pink salmon populations indices for various stages of the life cycle. The survival measured as the recruits number per parental stock (R/S) has a non-linear dependence on this environmental indices described by parabolic equations. These dependencies are used in reproductive models, which simulate observed fluctuations of R/S with high accuracy. Note that these environmental factors influence on the pink salmon survival is opposite for its odd and even generations. For example, high PDO value in November is unfavorable for survival of the pink salmons in East Kamchatka in the first year of their life (incubation) but favorable for survival of the same population in the second year (marine feeding) - that’s why strong and weak year-classes of pink salmon are alternated. Both PDO and WP indices have quasi-biennial periodicity that is a bit longer than the 2-year alternation of the pink salmon generations, hence favorable environments change their correspondence with odd or even generations from time to time, on average in approximately every 8 years. Similar regularities are supposed for other salmon species, as West Kamchatka coho salmon.